PELATIHAN PEMBUATAN TEPUNG BIJI SORGUM PUTIH DENGAN PENAMBAHAN KONSENTRASI RAGI DI DESA BOAK KELURAHAN UNTER IWES KABUPATEN SUMBAWA - Afgani, Chairul Anam; Nairfana, Ihlana; Azis, Lukman; Mikhratunnisa, Mikhratunnisa (Universitas Muhammadiyah Mataram, 2021)
Sorghum is one of the cereal commodities that is quite well used in the manufacture of flour. In Indonesia, the utilization of sorghum seeds is still not maximally used. At this time, sorghum seeds are used as animal feed and boiled directly for consumption. The aim of manufacture of white sorghum seed flour with the addition of yeast in Boak Village, Unter Iwes was to extend shelf life and facilitate its use. The provision of knowledge is done by providing socialization, discussion and practice. The results show that the community understood sorghum seeds as flour in the manufacture of food and processed with a good quality. Processing sorghum seeds with the addition of yeast is a way to extend the shelf life of sorghum and make it easier to be processed into various food products.